Commitment Mediates, Culture Moderates: How Learning Impacts Performance at an Energy Company - Sulistyaningsih, Endang; Pangalila, Tamara Setyowati (Journal of Management and Business Environment (JMBE), 2024)
This research aims to analyze the influence of organizational learning on employee performance at Energy Company, with organizational commitment as a mediating variable and organizational culture as a moderating variable. The population in this study consists of 59 permanent employees of the Energy Company residing in Jakarta, Indonesia, with a sample of 52 employees. Data collection was carried out using a questionnaire distributed to Energy Company employees. The data analysis technique used multiple linear regression analysis operated with the Hayes Process Macro SPSS. The study results show that organizational learning significantly influences employee performance and organizational commitment, and organizational commitment significantly influences employee performance. Organizational commitment also partially mediates the influence of organizational learning on employee performance. However, organizational culture needs to moderate the impact of organizational learning on employee performance. This study contributes to understanding how multinational energy companies manage and support their employees in diverse cultural settings.